MEWUJUDKAN GENERASI SADAR PAJAK MELALUI PENDIDIKAN INKLUSI KESADARAN PAJAK: STUDI KASUS PADA UNIVERSITAS SELAMAT SRI - Arina Hidayati; Tri Joko Sulistiyanto; Farah Dzil Barr (Jurnal Utilitas, 2022)
Tax Consciousness Inclusive Education is a program created by Ministry of Finance and Ministry of Research, Technology, and High Education (Indonesian: Kemenristek Dikti). Universitas Selamat Sri (UNISS) is one of universities, with 60% working students. However, the authors' preliminary observation showed only 10% of students having had Tax Identity Number (TIN or Indonesian: NPWP), and less than 10% of them having met taxpayers' obligation. The fact made the author interested in finding out "how is the tax consciousness inclusive education applied to UNISS?” This research was conducted using qualitative method with case study design. Meanwhile, data collection was done using three techniques: interview, observation, and documentation study. Technique of analyzing data used was Spradley's domain analysis, in which the data obtained would be processed through triangulation validity test technique. The tax consciousness inclusive education in UNISS is implemented through internalizing it into the learning of General Compulsory Course and taxing course, and technical guide for lecturers and establishment tax volunteer group for lecturers and students.